Effect of Flipped Instructional Strategy on Performance and Motivation in Wave Concept among Low-Achieving Secondary School Physics Students in Zaria, Kaduna State, Nigeria - Sani, Mustapha Bichi; Shuaibu, Zainab Ahmad; Babajo, Ismail; Raymond, Mela (Kashere Journal of Education, 2025)
This study examined the effect of a flipped instructional strategy on motivation and performance in the wave concept among low-achieving secondary school physics students in Zaria, Kaduna State, Nigeria. The study employed a quasi-experimental design involving pretest and posttest control groups. The population of the study comprises all public co-educational Senior Secondary School II (SS2) Physics Students in the Zaria Education Zone of Kaduna State. In this study, the available data revealed that there were 3357 SSII students (2184 males and 1173 females) offering Physics in the Zone. The sample of the study comprised 115 SS II Physics low achievers (76 males and 39 females) from two (2) randomly selected public co-educational senior secondary schools in Zaria Education Zone. The study was guided by two objectives with their corresponding research questions and null hypotheses. Two instruments, the Wave concept Performance Test (WCPT) and the Wave Concept Motivation Questionnaire (WCMQ), were used to collect data. The instruments were validated by experts, and the reliability coefficients of WCPT and WCMQ were obtained as 0.84 and 0.76 using the Pearson Product Moment Correlation Coefficient (PPMCC) for WCPT and the Cronbach Alpha statistical tool for WCMQ, respectively. The data collected was subjected to analyses at two different levels via descriptive and inferential statistics. The descriptive statistics of mean, standard deviation, and sum of Rank were used to answer the research questions raised. While at the inferential level, t-test and Mann-Whitney U-test analyses were used to test the null hypotheses at the significance level of α ≤ 0.05. The inferential statistics level forms the basis for a decision on whether to reject or retain the null hypotheses after they have been tested. The results showed that low-achieving students who learned the wave concept using Flipped Instructional Strategy performed significantly better than those who learned it through the traditional method (p=0.000). There was a significant difference in the motivation levels of students taught the wave concept using FIS compared to those taught using the conventional method, with the experimental group showing higher motivation (p=0.000). Based on the findings of the study, it was recommended, among others, that Physics teachers should be encouraged through training and retraining programmes by state Ministry of Education and professional bodies such as STAN on the use of FIS in teaching Physics concept like wave, as it enhanced students’ motivation and academic performance